2022
DOI: 10.3390/educsci12030205
|View full text |Cite
|
Sign up to set email alerts
|

Cohort-Based Education and Other Factors Related to Student Peer Relationships: A Mixed Methods Social Network Analysis

Abstract: Graduate students face a variety of stressors that relate to poor academic performance, lower completion rates, and high rates of depressive symptoms, anxiety, and stress. Student peers provide supports for coping with these stressors and succeeding academically. However, graduate students may find it difficult to form relationships with their peers. This mixed method social network analysis (MMSNA) examines graduate student perceptions of their peer relationships and the factors associated with peer friendshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
(120 reference statements)
0
1
0
Order By: Relevance
“…It is more possible to succeed for students who are fully integrated into social relationships in college (Tinto et al, 1993). Mauldin (2022) pointed out that social integration should be examined in respect of individual attributes and cohort-based learning. The influences of peer groups on student engagement rely on teacher involvement (Vollet et al, 2017) and thereby contributions to student engagement require an understanding of the joint effects of high teacher involvement and peer relationships.…”
Section: Resultsmentioning
confidence: 99%
“…It is more possible to succeed for students who are fully integrated into social relationships in college (Tinto et al, 1993). Mauldin (2022) pointed out that social integration should be examined in respect of individual attributes and cohort-based learning. The influences of peer groups on student engagement rely on teacher involvement (Vollet et al, 2017) and thereby contributions to student engagement require an understanding of the joint effects of high teacher involvement and peer relationships.…”
Section: Resultsmentioning
confidence: 99%
“…In smaller cohorts, there is a limited set of student data (attendance, interactions, use and diversity of learning material, sources and concepts generated, number and types of feedback), but, nevertheless, these limited attributes successfully predict students' interim and final marks, as argued by Wakelam et al [12]. During the study, students faced different stressors which might affect poor academic performance and lower completion rates, which is more evident in smaller cohorts and among first-year students where the number of peer interactions is smaller and value sharing is reduced [13]. Moreover, a larger diversity across students' age, gender, and even culture may provide an environment in which students from underprivileged communities (physical or virtual) may experience robust social engagement in learning [13].…”
Section: Introductionmentioning
confidence: 92%
“…During the study, students faced different stressors which might affect poor academic performance and lower completion rates, which is more evident in smaller cohorts and among first-year students where the number of peer interactions is smaller and value sharing is reduced [13]. Moreover, a larger diversity across students' age, gender, and even culture may provide an environment in which students from underprivileged communities (physical or virtual) may experience robust social engagement in learning [13]. Mauldin et al [13] also found that students in small cohorts are more frequently physically isolated from their peers than their counterparts in larger cohorts (in terms of lab work and time spent out of campus).…”
Section: Introductionmentioning
confidence: 99%
“…Homogeneity, i.e., having characteristics that are similar in some way, can explain the formation of peer relationships, and college students tend to form friendships with classmates of the same age, gender, and race [32]. For example, female students are more likely to form peer relationships based on gender and age similarity, and both genders equally tend to form relationships based on informedness similarity regarding the content and study conditions of their study program [33].…”
Section: Peer Relationships Of College Studentsmentioning
confidence: 99%